BUSINESS SIMULATION AS KEY MOTIVATION FACTOR IN STIMULATING BUSINESS INTENTION AMONGST UNIVERSITY STUDENTS IN MALAYSIA - Mohd Sufli Yusof (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2021)
The importance to raise up the number of entrepreneurs among the younger generation, especially among the university’s students has been recognized by the Government. This study seeks to link the effectiveness of business simulation with entrepreneurship interest of the students in University Utara Malaysia, main campus, Sintok. Four main objectives of the study were highlighted which is to see the relationship of perception, learning, interest and satisfaction of the business simulation on the tendency of students to venture into the business environment. The fifth objective is the combination of perception, learning, interest and satisfaction from business simulations of their entrepreneurial tendencies. The findings show that there is a significant relationship between learning, interest, satisfaction and the combination of all dimensions-dimensions of the business tendency. The findings from this study particularly useful to certain parties in the field of education and also to entrepreneurial developers.